1993
DOI: 10.1161/01.cir.88.3.1063
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent electrophysiologic effects of amiodarone in humans.

Abstract: The frequency-dependent response of the electrophysiologic effects of amiodarone are similar after 11 days of loading or > or = 1 year of chronic therapy. Amiodarone does not exert frequency-dependent effects on ventricular repolarization; it prolongs refractoriness by both time- and voltage-dependent mechanisms and exerts frequency-dependent effects on ventricular conduction. The absence of amiodarone-induced reverse frequency-dependent effects on repolarization, together with its time-dependent effects on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 62 publications
3
33
0
1
Order By: Relevance
“…However, it has been reported that some antiarrhythmic drugs induced postrepolarization refractoriness in the myocardium. [13][14][15] Although compared with the class I antiarrhythmic drugs, postrepolarization refractoriness would be less prominent in class III antiarrhythmic drugs, it could modulate the reasonable relationship between the ERP and ARI observed in the control state of the present study. To clarify this point, the same type of analysis was performed in patients treated with dl-sotalol, and the result showed that the ARI in the dl-sotalol group corresponded as well to the ERP as in the control group.…”
Section: Discussionmentioning
confidence: 75%
“…However, it has been reported that some antiarrhythmic drugs induced postrepolarization refractoriness in the myocardium. [13][14][15] Although compared with the class I antiarrhythmic drugs, postrepolarization refractoriness would be less prominent in class III antiarrhythmic drugs, it could modulate the reasonable relationship between the ERP and ARI observed in the control state of the present study. To clarify this point, the same type of analysis was performed in patients treated with dl-sotalol, and the result showed that the ARI in the dl-sotalol group corresponded as well to the ERP as in the control group.…”
Section: Discussionmentioning
confidence: 75%
“…18,19 In humans, the prolongation of repolarization rarely exceeds 10% to 15%, as assessed with surface ECG 20 or monophasic action potential (MAP) recording. 21,22 Early on, Drvota and coworkers 4 performed in vitro experiments suggesting that the effects of DEA on cardiac electrical activity could depend on gene expression. In their extensive 1997 review, Kodama et al 15 expression of Kv1.5 (KCNA5) in rats treated with amiodarone.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…5,8,22 The multiple ion channel interaction by amiodarone has been speculated to contribute to its minimal reverse use dependency and low incidence of clinical TdP arrhythmias, even in patients who develop TdP on other antiarrhythmics. 5,[22][23][24] Dronedarone, given either long-term or shortterm, has been suggested to possess a similar electrophysiological profile, but the effects of chronic dronedarone on specific cardiac ion channels are still unknown. [7][8][9] Arrhythmic Parameters: Dispersion…”
Section: Van Opstal Et Al Amiodarone In An Animal Model Of Acquired Lmentioning
confidence: 99%